Adaptive Automation, Level of Automation, Allocation Authority, Supervisory Control, and Adaptive Control: Distinctions and Modes of Adaptation - Sheridan, T B (IEEE transactions on systems, man and cybernetics. Part A, Systems and humans, 2011)
This paper revisits several concepts and model frameworks that have been in the literature of human-machine interaction and control engineering for up to 50 years. The purposes of the revisit are as follows: 1) to sharpen distinctions between adaptive automation, level of automation, allocation authority, supervisory control, and adaptive control engineering as the terms are currently used in the literature; 2) to define modes of human supervisory adaptation from the control engineering perspective; and 3) to suggest comparative taxonomies for adaptive automation in direct control and in supervisory control.